2009
DOI: 10.1001/archsurg.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

Racial Clustering and Access to Colorectal Surgeons, Gastroenterologists, and Radiation Oncologists by African Americans and Asian Americans in the United States

Abstract: Increasing numbers of minority patients in counties is accompanied by a differential access to specialists. This may affect the likelihood of a patient to receive appropriate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
1
43
2
Order By: Relevance
“…Rural residents with cancer may be at highest risk for receiving care across geographic divides, and the danger of poor collaboration may be further heightened by an oncologic workforce in these communities that is understaffed and experiences high turnover rates. [55][56][57][58][59] Although prior literature has demonstrated associations between higher patient sharing and lower cost among patients with chronic illnesses and in cancer survivorship care, 23,60 we did not find a statistically significant cost savings associated with patient sharing among the patients with stage III colon cancer in our study. There are considerable costs associated with guideline-concordant treatment for stage III colon cancer, including initiation of adjuvant chemotherapy within 4 months of diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…Rural residents with cancer may be at highest risk for receiving care across geographic divides, and the danger of poor collaboration may be further heightened by an oncologic workforce in these communities that is understaffed and experiences high turnover rates. [55][56][57][58][59] Although prior literature has demonstrated associations between higher patient sharing and lower cost among patients with chronic illnesses and in cancer survivorship care, 23,60 we did not find a statistically significant cost savings associated with patient sharing among the patients with stage III colon cancer in our study. There are considerable costs associated with guideline-concordant treatment for stage III colon cancer, including initiation of adjuvant chemotherapy within 4 months of diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…Haas et al also reported that living in counties with diminished capacity for colonoscopy had a marginal association with increased late-stage CRC at the time of diagnosis. Minority populations are more likely to reside in areas with an inadequate supply of gastroenterologists, 22,36 and there is a persistent shortage of specialists, including gastroenterologists, in rural areas. 33,37 Based on the above findings, minority and rural populations could be at increased risk for late-stage CRC diagnosis and poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 More recent studies have suggested that differences in the receipt of appropriate care 7,9 and the location of care may also predict survival after treatment for cancer. [14][15][16] These studies suggest that minorities cluster for care in low-performing hospitals 17,18 or hospitals that fail to adhere to evidence based care delivery. 19 Each of these studies highlights the link between location of care, cancer survival, and disparities.…”
Section: Introductionmentioning
confidence: 99%